KAJIAN KOEFISIEN UPAH KERJA PEKERJAAN PEMASANGAN BATA RINGAN PADA PEMBANGUNAN GEREJA KRISTEN INDONESIA BROMO KOTA MALANG - Suhudi Suhudi; Reynold J. A. Telnoni (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2018)
In a construction project either in the planning, implementation and supervision of construction management indispensable good. It is intended that a project can run well, with cost-efficient and can be implemented on time. The method of implementation is an important part in the implementation of a project. What is important is the coefficient of wages as this will greatly affect the welfare of the workers. The determination of the coefficient of wages must be referring to the Indonesian National Standard (SNI). Light brick is a material that is widely used today. However, SNI has not been set on the coefficient of light brick work itself so that the implementation of the field is still used coefficient of wages for work of red brick. Calculating the coefficient of wages is by dividing the daily work volume and number of employees as a factor denominator. From observations made on the installation work light brick building Gereja Kristen Indonesia Bromo, the method used is correct. From the analysis of the data for wage coefficients obtained total wage employment lightweight brick installation methods SNI Rp 76.12 million, while total wages fact the field installation of light brick Rp 63.106 million, and based on research wages brick work lighter by Rp78.955 million, For the cost/m2 installation of lightweight brick according to SNI is Rp 29909.88. While the value of wage employment per m2 installation of lightweight brick according to the reality on the ground is Rp 24797.08 difference between the two comparisons is Rp 5112.8. Cost saving light brick work execution reached 17%.